Distribution Of fasciculations in healthy adults after exercise: An ultrasound study. Issue 1 (19th May 2016) - Czell, David; Goldman, Beatrice; Weber, Markus
ABSTRACT: Introduction: Ultrasound has become a reliable method to detect fasciculations. There is disagreement as to whether fasciculations above the knee should raise the suspicion of a disorder even if there are no other signs of lower motor neuron abnormality. Methods: Using ultrasonography, 3 arm and 3 leg muscles were investigated for 120 s, 45 min after 90‐min handball training or a 5, 000 meter run in a group of 25 men and 25 women handball players and 7 men who are amateur runners. Results: All athletes had fasciculations in muscles above the knee. There were no fasciculations in the upper limb muscles in the runner group. In 21 men and 18 women handball players between 1 to 17 fasciculations in 2 min were detected. The number of fasciculations in the rectus femoris was 4‐fold higher in the runners compared with the handball players (ratio 0.24; P  = 0.037). Conclusions: Fasciculations may occur in muscles above the knee in healthy subjects. The distribution of fasciculations primarily depends on the exercised muscles. Muscle Nerve, 2016 Muscle Nerve 54 : 132–135, 2016 Muscle Nerve 54 : 132–135, 2016